One-dimensional arrangement of nanoparticles utilizing the V-groove and cage shaped proteins. (24th May 2017) - Ban, Takahiko; Uenuma, Mutsunori; Migita, Shinji; Okamoto, Naofumi; Ishikawa, Yasuaki; Uraoka, Yukiharu; Yamashita, Ichiro; Yamamoto, Shin-ichi
Abstract: The one-dimensional arrangement of nanoparticles (NPs) was performed using a V-groove and ferritins as spherical shell proteins. The V-groove was synthesized by lithography and anisotropic etching of a Si substrate. Ferritin has an outer diameter of 12 nm and an inner diameter of 6 nm, and various inorganic substances can be formed into the cavity. In this study, iron oxide, cobalt oxide, and indium oxide cores were used. The surface potential of ferritin can be changed by genetic modification. Particularly, by using Fer8-K98E, NPs could be arranged one-dimensionally onto the bottom of the V-groove. In addition, we succeeded in selectively forming a one-dimensional array of one layer, two layers, and three layers by changing the protein concentration. This experiment is expected to be applicable to various one-dimensional devices.